PENGEMBANGAN MODEL PEMBELAJARAN SAINS BERBASIS ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) ATAU TIK (TEKNOLOGI INFORMASI DAN KOMUNIKASI) DI SEKOLAH DASAR - Sulistyorini, Sri (Universitas Negeri Semarang, 2014)
The problemsof this researchare:1)how todevelop sciencelearning material based on ICT, 2) how are teacherâs skills inlearning process based onICT, 3) how are thestudentsâactivities duringlearning process based onICT, 4) how are the studentsâ learning outcomes based on ICT, and 5) how are studentsand teachersresponsein learning process based on ICT? This research approach isResearchand Development(R &D). The subjects of this research are the fifth grade students andteacher of Al-Madina Primary school in Semarang. Techniques of Data Collection are observations,interviews, questionnaires, testsanddocumentations. The data analysisis descriptive statistics. The research finding showsthat development of Science learning based onICT in animalsand plantsadaptation competency can effectivelyincrease the studentsâ activity, it is shown that students work dominantly using computer as alearning media, teachers usuallyimplement learning based on ICT, it can complete the studentslearning outcomesalso studentsand teachersresponsetowardlearning process based on ICTbelong to good.